Pharmacotherapy for methadone-induced erectile dysfunction: A meta-analysis - Yee, A.; Loh, H.S.; Sulaiman, A.H.; Ng, C.G. (Associazione per l'Utilizzo delle Conoscenze Neuroscientifiche a fini Sociali, 2016)
Summary Background: Methadone is recognized as an effective maintenance therapy for opioid dependence. Of the many adverse events reported, sexual dysfunction is the most common. To date, however, no standard treatments have been made available to this subgroup of patients. Aim: We conducted a meta-analysis to assess 2 therapeutic options – adjunctive medication or switching to buprenorphine – for treating sexual dysfunction among male patients on methadone maintenance therapy. Methods: Pertinent English-language studies published from inception until January 2016 were identified by searching through PubMed, OVID, Embase, PsycArticles EBSCO, Cochrane Library, and Google Scholar databases. Studies were selected using previously defined criteria. Heterogeneity, publication bias, odds ratios, and effect size were all assessed thoroughly. Results: In all, 826 male participants selected from 11 eligible studies were identified in this meta-analysis. The effect size of treatment with adjunctive medication was at least 3.8 (95% confidence interval [CI] = 2.5–5.2, p < 0.0001) times greater than that before the intervention. The odds of erectile dysfunction occurring in men treated with methadone were 5.6 times greater (95% CI = 0.06–0.6, p < 0.01) than that in men treated with buprenorphine. Similarly, the odds of sexual desire being lost in men receiving methadone were 14.3 times greater (95% CI = 0.04–0.2, p < 0.01) than those in men receiving buprenorphine. Conclusions: Evidence shows that switching to buprenorphine or using adjunctive treatment reduces sexual dysfunction among male patients on methadone.